2015
DOI: 10.3382/ps/pev111
|View full text |Cite
|
Sign up to set email alerts
|

Dose titration of FITC-D for optimal measurement of enteric inflammation in broiler chicks

Abstract: Traditionally, antibiotic growth promoters (AGP) have been used in foodstock animals to reduce enteric inflammation and maintain intestinal homeostasis, thus improving growth and performance. Due to increasing restrictions regarding the use of AGP however, precise and high throughput enteric inflammation models and markers to search for effective alternatives are urgently needed. In this paper, oral administration of fluorescein isothiocyanate dextran (FITC-d, 3-5 kDa) and its passage into blood was used as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
99
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(108 citation statements)
references
References 23 publications
6
99
2
1
Order By: Relevance
“…The interaction between the LPS dose and time points for individual sugars was not statistically significant. In addition, birds in these experiments were fasted for 19.5 h and recently it has been shown that 24 h fasting increased IP in chickens (Kuttappan et al, 2015;Vicuna et al, 2015b). To exclude the possible interference of fasting with LPS, a third experiment at 1 mg/kg BW without fasting was conducted.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The interaction between the LPS dose and time points for individual sugars was not statistically significant. In addition, birds in these experiments were fasted for 19.5 h and recently it has been shown that 24 h fasting increased IP in chickens (Kuttappan et al, 2015;Vicuna et al, 2015b). To exclude the possible interference of fasting with LPS, a third experiment at 1 mg/kg BW without fasting was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…These variations and limited published data may need further investigations. Fluorescein isothiocyanate dextran has a high molecular weight of 40 kDa and increased serum concentrations indicate increased IP in chickens (Kuttappan et al, 2015;Vicuna et al, 2015a and2015b). However, DSS ingestion and fasting were utilized as models of increased IP, compared with the LPS model in the current studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations